Improving the quality of clinical research on chronic wound infection treatment: expert-based recommendations. (1st January 2019) - Pomponio, Giovanni; Tedesco, Silvia; Peghetti, Angela; Bianchi, Tommaso; Rowan, Sara; Greco, Alessandro; Cutting, Keith; Price, Patricia; Moore, Zena; Gabrielli, Armando; Wolcott, Randall
Abstract : Objective: To produce recommendations for the design of reliable and informative clinical investigations in chronic wound infection. Method: A multidisciplinary panel of international experts from four countries (Italy, UK, Ireland and the US) were involved in a detailed, semi-structured discussion on how to better select and describe a target population, interventions and outcomes, and which infection-related criteria to apply in order to achieve a high-quality trial. Consent among the experts was measured using the Delphi method and GRADE Working Group suggestions. The project was fully supported by AISLeC 2016 (Italian Nursing Society for Wound Care Study). Results: In total, 37 recommendations achieved substantial agreement among the experts; 10 concerned the most appropriate description and selection of a target population, four related to interventions and 15 to outcomes. A further eight statements about critical methodological points were approved. Conclusion: Developing recommendations in a systematic manner through a representative group of experts could generate tools for improving the design of clinical trials in this challenging area.